Rotorcraft Icing - Progress and Potential. - ADVISORY GROUP FOR AEROSPACE RESEARCH AND DEVELOPMENT NEUILLY-SUR-SEINE (FRANCE) (1986)
Helicopter icing remains a significant operational consideration for military helicopters operating throughout Europe and Northern parts of North America. Following the finding of AGARD Advisory Report No.166 'Rotorcraft Icing-Status and Prospects' (August 1981), further collaboration was considered beneficial to address the following objectives: 1) to proceed with the recommendations of the original group on rotorcrafting; 2) to examine rotorcraft icing analysis and modeling; 3) to consider new methods of ice protection; and 4) to compare operational experience with ice protected rotorcraft with the design and qualification criteria presently established. This report contains the findings of an international Working Group including a comparison of icing atmosphere models and forecasting techniques; and an assessment of predictive methods and simulation, flight clearance strategies and requirements. It closes by considering various new methods of icing protection for rotorcraft.